Transitivité partielle de la synonymie : application aux dictionnaires de synonymes - Jean-Luc Manguin (Corela, 2004)
As a starting point, we assume that our model of the relation of synonymy is an undirected graph, in which the nodes are lexical units, and the edges are synonymic links ; then we propose an automatic method for enriching or checking the dictionary figured by this graph. Our method is based on similarity indexes between the nodes of the graph ; according to some criteria that will be defined, our process can add direct links from a node to some of its 2-order synonyms. We will test this process on a real dictionary (René Bailly’s) in its electronic form, and we will examine the quality of the results. Finally we will apply the process to a larger dictionary (made by merging some real dictionaries) before we conclude.